Indigenous legal traditions (Legal dimensions series, 2007)
"The essays in this book present important perspectives on the role of indigenous legal traditions in reclaiming and preserving the autonomy of Aboriginal communities and in reconciling the relationship between these communities and Canadian governments. Common threads linking the essays include the relationship between indigenous and Canadian legal orders, the importance of indigenous legal traditions for Aboriginal communities' autonomy, and the ways in which these traditions might be recognized and given space in the Canadian legal landscape." "In its examination of different aspects of and models for the recognition of indigenous legal orders, this book addresses important issues relating to legal pluralism. It will be of interest to a wide audience including lawyers and legal academics, teachers, students, policy makers, and members of Aboriginal communities."--Jacket